Influence of Se-doping and/or Bi addition on microstructure and thermoelectric properties of Cu0.05Bi2Te3. Issue 1 (January 2017) - Chen, Song; Cai, Kefeng; Shen, Shirley
Abstract: Cu0.05 Bi2 Sex Te3−x (x=0.2, 0.3, 0.4) bulk samples were prepared by hot pressing corresponding nanopowders synthesized by a gas-induced reduction method. Se doping significantly increases the carrier concentrations and hence the electrical conductivities of the samples. Based on this, a Cu0.05 Bi2 Se0.3 Te2.7 sample with a higher power factor was chosen as a pristine sample; some of the Cu0.05 Bi2 Se0.3 Te2.7 nanopowders were mixed with various amounts of Bi nanoparticles (NPs) and then hot pressed into bulk samples. The addition of Bi NPs promotes the sintering of samples. When the content of Bi NPs added is low (≤1 wt%), the electrical conductivity is higher than the pristine sample, and all the Bi NPs added samples have higher Seebeck coefficient than the pristine sample, hence, the power factor has been improved. A maximum power factor, 30.6 µWcm −1  K −2, has been obtained for the 2 wt% Bi NPs added sample.